2016
DOI: 10.1098/rsob.160287
|View full text |Cite
|
Sign up to set email alerts
|

Genome recoding by tRNA modifications

Abstract: RNA modifications are emerging as an additional regulatory layer on top of the primary RNA sequence. These modifications are particularly enriched in tRNAs where they can regulate not only global protein translation, but also protein translation at the codon level. Modifications located in or in the vicinity of tRNA anticodons are highly conserved in eukaryotes and have been identified as potential regulators of mRNA decoding. Recent studies have provided novel insights into how these modifications orchestrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 92 publications
(142 reference statements)
0
63
0
Order By: Relevance
“…Cytosine‐5 methylation (m 5 C) is a widely known modification in the context of DNA methylation and epigenetic gene regulation (Jones, ). Interestingly, m 5 C also represents a conserved RNA modification (Gilbert et al , ), and several recent studies have provided evidence for a conserved role in the regulation of protein translation (Tuorto & Lyko, ). We have previously shown that Dnmt2‐mediated tRNA methylation affects the speed and accuracy of protein translation (Tuorto et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Cytosine‐5 methylation (m 5 C) is a widely known modification in the context of DNA methylation and epigenetic gene regulation (Jones, ). Interestingly, m 5 C also represents a conserved RNA modification (Gilbert et al , ), and several recent studies have provided evidence for a conserved role in the regulation of protein translation (Tuorto & Lyko, ). We have previously shown that Dnmt2‐mediated tRNA methylation affects the speed and accuracy of protein translation (Tuorto et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…3). Individual anticodon domain modified nucleosides are identity determinants for protein recognition, particularly aminoacylation, 15-17 increase accuracy and efficiency in codon recognition, 18-24 and pre-structure the ASL for translation. 9,25-30 Each of the modified nucleosides contribute distinct chemistries, nucleoside conformations and dynamics, and their contributions to decoding have been studied extensively over decades and most recently reviewed.…”
Section: The Importance Of Being Modifiedmentioning
confidence: 99%
“…9,25-30 Each of the modified nucleosides contribute distinct chemistries, nucleoside conformations and dynamics, and their contributions to decoding have been studied extensively over decades and most recently reviewed. 20,22,24,28,31-38 However, there is significant evidence that a combination of two or three anticodon domain modifications play a synergistic role in tRNA function where modification of a wobble position U is crucial. 9,20,24,39-46 Today, we know that certain modifications of U 34 enable expansion of codon from NNA/G recognition to synonymous codons ending in pyrimidines, N1-N2-Pyr, where N is any of the 4 nucleosides and Pyr is either U or C. 29 Yet, the anticodon domain of some tRNA species lack modification and can be totally devoid of modified nucleosides.…”
Section: The Importance Of Being Modifiedmentioning
confidence: 99%
“…Second, anticodons corresponding to sense codons are often the most important recognition element for aaRSs (39, 64); therefore, the three recoded genome projects are carefully focusing on Ala, Ser, and Leu codons whose cognate aaRS enzymes do not recognize the anticodon as an identity element (71, 113, 149). In addition, base modification of tRNAs is also important for accurate translation and restricted/extended codon decoding by tRNA (40) in not only a static but also a dynamic manner (142). Modified or unmodified U34 in an anticodon could be paired with any nucleotide at the wobble position of codons in the ribosome.…”
Section: Preparing For Radically Altered Genetic Codesmentioning
confidence: 99%